A Literature Study On The Negative Impact Of Youtube As An English Language Learning Media - Ahmad Julianto; Zaitun Qamariah (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
This study discusses the negative impact of YouTube on learning English. This is due to advances in technology and information that have caused many users to use applications, one of which is YouTube which is used as a learning medium, but they are not aware of the effects that will occur if they cannot regulate what they use. they see or hear. Literature research was used in writing this article, which includes collection and analysis from various sources, such as documents, books (e-books), research journals, and other related online articles. After collecting the necessary data, the author reads and documents sources that relate to the topics discussed. The results of the study show that there are many negative impacts of YouTube that arise because of a lack of understanding in selecting quality English learning materials.